2016 SIIL Annual Meeting - Geospatial and Farming Systems Research Consortium - Hijmans R.J. (Kansas State University, 2016)
Dr. Robert Hijmans, Director of the Geospatial and Farming Systems Research Consortium of the Feed the Future Innovation Lab for Collaborative Research on Sustainable Intensification, presents his project to the SIIL community. Filmed in January 2016.